Nitrosylation of Nitric‐Oxide‐Sensing Regulatory Proteins Containing [4Fe‐4S] Clusters Gives Rise to Multiple Iron–Nitrosyl Complexes. Issue 47 (25th October 2016) - Serrano, Pauline N.; Wang, Hongxin; Crack, Jason C.; Prior, Christopher; Hutchings, Matthew I.; Thomson, Andrew J.; Kamali, Saeed; Yoda, Yoshitaka; Zhao, Jiyong; Hu, Michael Y.; Alp, Ercan E.; Oganesyan, Vasily S.; et al.
Abstract: The reaction of protein‐bound iron–sulfur (Fe‐S) clusters with nitric oxide (NO) plays key roles in NO‐mediated toxicity and signaling. Elucidation of the mechanism of the reaction of NO with DNA regulatory proteins that contain Fe‐S clusters has been hampered by a lack of information about the nature of the iron‐nitrosyl products formed. Herein, we report nuclear resonance vibrational spectroscopy (NRVS) and density functional theory (DFT) calculations that identify NO reaction products in WhiD and NsrR, regulatory proteins that use a [4Fe‐4S] cluster to sense NO. This work reveals that nitrosylation yields multiple products structurally related to Roussin's Red Ester (RRE, [Fe2 (NO)4 (Cys)2 ]) and Roussin's Black Salt (RBS, [Fe4 (NO)7 S3 ]. In the latter case, the absence of 32 S/ 34 S shifts in the Fe−S region of the NRVS spectra suggest that a new species, Roussin's Black Ester (RBE), may be formed, in which one or more of the sulfide ligands is replaced by Cys thiolates. Abstract : Nuclear resonance vibrational spectroscopy of NO‐sensing proteins WhiD and NsrR reveal products of [4Fe‐4S] cluster reactions with NO related to Roussin's Red Ester (RRE) and Roussin's Black Salt (RBS) species. RBS itself was not a product, but instead the results point to a new Roussin's Black Ester species featuring Cys thiolate coordination in place of sulfide.